2020
DOI: 10.3390/app10072581
|View full text |Cite
|
Sign up to set email alerts
|

Business Analytics in Telemarketing: Cost-Sensitive Analysis of Bank Campaigns Using Artificial Neural Networks

Abstract: The banking industry has been seeking novel ways to leverage database marketing efficiency. However, the nature of bank marketing data hindered the researchers in the process of finding a reliable analytical scheme. Various studies have attempted to improve the performance of Artificial Neural Networks in predicting clients’ intentions but did not resolve the issue of imbalanced data. This research aims at improving the performance of predicting the willingness of bank clients to apply for a term deposit in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 36 publications
(86 reference statements)
1
32
0
Order By: Relevance
“…Ghatasheh et al [5] Business analytics in telemarketing: cost-sensitive analysis of bank campaigns using artificial neural networks -Artificial neural networks -Support vector machine -Random forest…”
Section: Authors Title Models Number Of Input Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Ghatasheh et al [5] Business analytics in telemarketing: cost-sensitive analysis of bank campaigns using artificial neural networks -Artificial neural networks -Support vector machine -Random forest…”
Section: Authors Title Models Number Of Input Featuresmentioning
confidence: 99%
“…Experimental results showed that the long short-term memory model using SMOTE outperformed other models. Ghatasheh et al [5] proposed an ANN model for bank telemarketing prediction using 16 variables and compared the performance of traditional machine-learning classifiers. They found that, the Type II and Type I errors of their proposed model were higher and lower, respectively, than those of other models.…”
Section: Outbound Telemarketingmentioning
confidence: 99%
See 1 more Smart Citation
“…The main issue with the bank is how to get correct prediction ratio during the direct marketing campaign. The idea was presented in the study [2] where the researcher proposed the artificial neural net model to forecast the chances of customers who can apply for short and long term deposits in the bank. Furthermore, the research incorporated by defining the rules, which can be helpful for the decision makers to understand the potential benefits that can be achieved through the marketing campaign.…”
Section: Related Workmentioning
confidence: 99%
“…To provide some ease in this operation, researchers have proposed several strategies integrated with use of latest technologies. For example business analytics in telemarketing using artificial neural networks [2] , chat-bot design on real marketing data [3] , and telemarketing forecasting using SVM [4] . Therefore, it can be evident that use of current technology can reveal many facts for the organizations by extracting hidden patterns from the collected dataset.…”
Section: Introductionmentioning
confidence: 99%